Fenômenos de instabilidade do arco na soldagem GMAW com gases de baixo potencial de oxidação - Maria Celeste Monteiro de Souza Costa (2006)
The arc welding process with continuous wire and gas protection (GMAW) is currently one of the most important metal joining process. This process has passed through a constant evolution with the introduction of power supplies with electronic control, and the use of techniques to control metal transfer, its operational stability and weld bead formation. Moreover, processes derived from GMA welding, aiming generally to ahigher productivity, have been developed in the last years. This welding process, however, is characterized by a strong interdependence of its operational parameters and a great sensitivity the small variations in its operational conditions. These characteristics tend to make it more difficult to reproduce welding conditions and can lead, in some instances, to conditions of instability and inadequate control of the process. These conditions can limit the application and reliability of this process and can increase the cost of the manufacture. The shielding gas plays different roles in GMA welding, beyond preventing the contamination of the liquid metal by the atmospheric air. In particular, the shielding gas affects the physical properties of the arc and the liquid metal, strongly influencing the transference of this metal through the arc, the stability of the process, bead formation and its fusion characteristics. Although these effects have already been extensively studied and many of their aspects are well known, lesser explored phenomena are observed in this process when the content of oxygen in the shielding gas is low. These seem to be associated with the conditions of electron emission in the arc and can cause strong alterations in the arc behavior, causing strong disturbances in operational conditions. In this work it is presented a study that involves the characterization of the instability in GMA welding in carbon and austenitic stainless steels, and pure aluminum with shielding gases of low potential of oxidation. The effect of these phenomena in operational characteristics of the process and bead fusion characteristics were also evaluated. The following general aspects were studied: characteristics of the instability in the three listed materials; metal transfer characterization by high speed filming synchronized with voltage and current signals of the process, weld bead shape in bead-on-plate welds and in narrow-gap grooves. It was observed that this instability associated to low oxidation potential of the shielding gas occurs in the three base metals although presenting some different characteristics.